Lightweight inter-cluster synchronization scheme for femtocell network - Hasb Alla, Omnya Abdel Rahman; A. Saeed, Rashid; Hassan, Kamarul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran (2013)
Femtocell is a small sized indoor basestation to increase the coverage and capacity. Femtocell is connected through broadband backhual to the IEEE1588 to synchronize and manage the network. Due to limited/poor connectivity femtocell suffers by frequency misallignment and clock differencs. To overcome this problem MS-Assisted Receiver-Receiver Time Synchronization Strategy has been proposed. But this strategy is not fully covered in all situations if there has no Mobile Station for a long time in any of fBS network and make network overhead by generating the message flooding for a big adjacent network. However, in this paper, lightweight inter -cluster synchronization scheme is proposed which functions through intra-cluster and inter-cluster synchronization scheme and added between them as enhancement intermediate nodes selection if the Cluster Head cannot see neighbor CH and by using the Hybrid Wireless Mesh Protocol (HWMP) to select one intermediate node, and so we get the best path to access neighboring CH to update clocks and synchronize the clusters. The proposed scheme provides high scalability and works in a decentralized manner. The analytical results show that synchronization accuracy can be achieved up to 60% higher than MS-Assisted Receiver-Receiver time synchronization strategy for femtocells.